Revitalizing Religious Programs in Elementary Schools Post Covid-19 - Zainal Abidin Muhja; Muqarranah Sulaiman Kurdi; Musyarrafah Sulaiman Kurdi; Eunike Rose Mita Lukiani; Pandu Adi Cakranegara; Deby Noviyanti (STAI Hubbulwathan Duri, 2023)
Religious programs cannot be carried out due to the Covid-19 Pandemic. However, after the repeal of PPKM, the school resumed carrying out the religious program. This study aims to analyze the school's efforts to revitalize religious programs when schools are allowed to hold face-to-face learning in line with the decline in the spread of Covid-19. The research method used is descriptive qualitative. Research informants are school principals, PAI teachers, and students. Collecting data through observation, interviews, and documentation. Data analysis through data reduction, data display, and drawing conclusions. This study found that the revitalization of religious programs was carried out after the program was not implemented optimally or even could not be implemented due to the Covid-19 Pandemic. This revitalization is essential as a form of school responsibility in strengthening character education, one of which is the religious program. The revitalized programs are 1) Quran recitation at the 0th hour, 2) commemoration of Islamic holidays, and 3) Yasin recitation. On the other hand, the school also revitalizes the teachers' understanding of the importance of religious education, teacher professionalism, and moral degradation as a challenge. Revitalizing religious programs can be done after the end of Covid-19 by revitalizing the program and teacher's understanding so that it can educate students' character through religious education in schools.